Moral enhancement, acquired virtue, and theism: A response to Brummett and Crutchfield. (31st July 2022) - Colgrove, Nicholas; McAllister, Derek; Rea, Burke
Abstract: Recently, Brummett and Crutchfield advanced two critiques of theists who object to moral enhancement. First, a conceptual critique: theists who oppose moral enhancement commonly do so because virtue is thought to be acquired only via a special kind of process. Enhancement does not involve such processes. Hence, enhancement cannot produce virtue. Yet theists also commonly claim that God is perfectly virtuous and not subject to processes. If virtue requires a process and God is perfectly virtuous without a process, however, then theists contradict themselves. Second, a moral critique: theists who reject moral enhancement are selfish, because accepting moral enhancement would (allegedly) reduce widespread suffering. Theists often condemn selfishness, however. By condemning selfishness and (simultaneously) rejecting enhancement, therefore, theists contradict themselves yet again. We argue that both critiques fail. Both substantially misrepresent their target. First, Brummett and Crutchfield confuse metaphysical enhancement (attempts to alter human nature ) with moral enhancement (attempts to become better human beings). Authors that Brummett and Crutchfield cite object to the former, not the latter. Second, both conceptual and moral critiques overlook the many resources within theistic traditions that can quickly resolve relevant (alleged) contradictions. The conceptual critique, for example, misrepresents both common views held among theists (regarding God's virtue) and the ways in which virtue may be acquired. Similarly, the moral critique mischaracterizes the relationship commonly posited by theists between enhancement and agency. By attending to what theists actually claim—rather than relying on caricatures—it becomes clear that each of Brummett and Crutchfield's critiques fail.